IMPLEMENTASI ROBOT HUMANOID SEBAGAI PEMBAGI BROSUR - Rouhillah (J-Innovation, 2015)
The distribution is an activity that is often carried out in various places, such as in schools, fairs, colleges, and other places. To attract the attention of visitors to want to take a proportion of the visitors reluctantly took a brochure distributed, because the distribution is less attractive, giving flyers with poor grammar, and disrespectful. In this study generated humanoid robot divider brochure with attractive looks, then the presence of this robot can help in the distribution process. This robot is equipped arm moves, sound, similar led eyes, and a mouth that serves to attract the attention of visitors to pick up a brochure distributed and process control using a microcontroller. The results of this study, the robotic arm can move, brochure paper can out one by one, and the robot can make a sound.